2008
DOI: 10.1111/j.1365-3059.2007.01778.x
|View full text |Cite
|
Sign up to set email alerts
|

Brenneria quercina and Serratia spp. isolated from Spanish oak trees: molecular characterization and development of PCR primers

Abstract: Brenneria quercina has been reported as one of the causal agents of oak decline in Spain. To investigate the bacterial variability of this pathogen from different Spanish oak forests, a collection of 38 bacterial isolates from seven geographic locations and from different oak species was analysed by sequencing 16S rDNA and rep-PCR fingerprinting. All Spanish isolates of B. quercina were grouped by rep-PCR into a homogenous cluster that differed significantly from B. quercina reference strains from California. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…Our analysis indicated that the Bq129/08 strain belongs to Lonsdalea quercina subsp. britannica taxon, which is known as an oak tree pathogen previously isolated in several different countries (Poza-Carrión et al 2008;Brady et al 2011). Because the symptoms of disease caused by L. quercina subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis indicated that the Bq129/08 strain belongs to Lonsdalea quercina subsp. britannica taxon, which is known as an oak tree pathogen previously isolated in several different countries (Poza-Carrión et al 2008;Brady et al 2011). Because the symptoms of disease caused by L. quercina subsp.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing with the rep‐PCR (repetitive element PCR fingerprinting technique) that was developed by Poza‐Carrión et al. () in the detection of L. quercina , real‐time PCR assay can rapidly identify and quantify the pathogen from genomic DNA, bacterial cells or directly from the tissue of field samples. This is because it has a number of specific advantages in the detection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecular diagnose methods is the Polymerase Chain Reaction (PCR) (Poza-Carrión et al, 2008;Frutos D, 2010). McClean et al (2008) developed real time PCR techniques based on the identification of B. rubrifaciens in inoculated soil and leaves, although they did not identify pure bacteria or infected samples.…”
Section: Molecular Techniquesmentioning
confidence: 99%
“…Dentro de los métodos moleculares de diagnós-tico se encuentra la Reacción en Cadena de la Polimerasa (PCR) (Poza-Carrión et al, 2008;Frutos D, 2010). McClean et al, (2008) desarrollaron técni-rubrifaciencies using the gene responsible for the synthesis of rubrifaciens, the red pigment produced by B. rubrifaciens, present in this species only, as the author indicates.…”
Section: Técnicas Molecularesunclassified